TABAYYUN VALUES MANIFESTATION IN NAHDATUL ULAMA AND MUHAMMADIYAH IN ORGANISAZING THE INFORMATION AND COMMUNICATION IN JAMBI CITY - Mira Susanti (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2022)
Abstract: This research is motivated by the rise of the phenomenon of negative news and hoaxes received by Nahdatul Ulama and Muhammadiyah. Hoax news is not without problems, destructive phenomena in society can be said to have started there, such as hate speech, discrimination, persecution, stereotypes and physical violence. However, the two Islamic groups are still rooted and legitimate in the religious consciousness of Indonesian Muslims. The researcher saw that there was a communication strategy used by the two organizations in response to negative issues thrown at them. So that they are not shaken and remain sociologically influential. This strategy is referred to as the tabayyun mechanism. With these logical reasons, researchers are trying to find out the concept and implementation of tabayyun within Nahdatul Ulama and Muhammadiyah in Jambi City. In order to reach that answer, the researcher used a qualitative research mechanism, by carrying out the process of observation, interviews and documentation. From the data analysis it was found that from within Nahdatul Ulama and Muhammadiyah had the same projection in building an understanding of tabayyun. However, the implementation is different for reasons of socio-cultural differences between the two religious groups. Both of them develop and adopt tabayyun strategies that rely on Islamic ethics in responding to negative or hoax news.